If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10d + 7 = 1 + 9d Reorder the terms: 7 + 10d = 1 + 9d Solving 7 + 10d = 1 + 9d Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-9d' to each side of the equation. 7 + 10d + -9d = 1 + 9d + -9d Combine like terms: 10d + -9d = 1d 7 + 1d = 1 + 9d + -9d Combine like terms: 9d + -9d = 0 7 + 1d = 1 + 0 7 + 1d = 1 Add '-7' to each side of the equation. 7 + -7 + 1d = 1 + -7 Combine like terms: 7 + -7 = 0 0 + 1d = 1 + -7 1d = 1 + -7 Combine like terms: 1 + -7 = -6 1d = -6 Divide each side by '1'. d = -6 Simplifying d = -6
| (3a^2)b= | | X+3X-4=6-2 | | 6x^4=0 | | 9x-2457=5x-160 | | -39+x=5x+7(x+7) | | -5=3/4x-2 | | r^2=16+9 | | 8d+18-d=d | | 65=35+a(3.4) | | 32+(3x)=12-x | | ny-6+y+8=42 | | 3(2+x)=10 | | 2.7b-9.8=15.2 | | -7-5/6x=18 | | (3/4)/(1/2) | | 4y+y+1=2z+13 | | A=9x+3xy | | 10b+10=8b-8 | | 15X+22=8X-11 | | 1=1/2x-3/4x | | 17=4x-16 | | 6X=17+1 | | 3k+4=2k | | 1-5n=1-5n | | 12+8x=5(x+8) | | 6X=17+11 | | 12y=3y+3z | | 3/76/x | | (2x-3)(4x+2)=0 | | -2f-4=-f | | 5(x+1)=2(3x-4) | | 43=2x-3 |